Influence of soot aerosol properties on the counting efficiency of instruments used for the periodic technical inspection of diesel vehicles - T. Hammer; D. Roos; B. Giechaskiel; A. Melas; K. Vasilatou (Aerosol Research, 2024)
In this work, we investigated the influence of different types of soot aerosol on the counting efficiency (CE) of instruments employed for the periodic technical inspection (PTI) of diesel vehicles. Such instruments report particle number (PN) concentration. Combustion aerosols were generated by a prototype bigCAST, a miniCAST 5201 BC, a miniCAST 6204 C, and a miniature inverted soot generator (MISG). For comparison purposes, diesel soot was generated by a Euro 5b diesel test vehicle with by-passed diesel particulate filter (DPF). The size-dependent counting efficiency profile of six PN–PTI instruments was determined with each one of the aforementioned test aerosols. The results showed that the type of soot aerosol affected the response of the PN–PTI sensors in an individualised manner. Consequently, it was difficult to identify trends and draw conclusive results about which laboratory-generated soot is the best proxy for diesel soot. Deviations in the counting efficiency remained typically within 0.25 units when using laboratory-generated soot compared to Euro 5b diesel soot of similar mobility diameter (∼ 50–60 nm). Soot with a mobility diameter of ∼ 100 nm generated by the MISG, the lowest size we could achieve, resulted in most cases in similar counting efficiencies as those generated by the different CAST generators at the same particle size, showing that MISG may be a satisfactory – and affordable – option for PN–PTI verification; however, further optimisation will be needed for low-cost soot generators to comply with European PN–PTI verification requirements.